Evolving Interplay Between Dietary Polyphenols and Gut Microbiota—An Emerging Importance in Healthcare - Ray, Suman Kumar; Mukherjee, Sukhes (Frontiers in Nutrition, 2021)
Polyphenols are naturally occurring compounds in plants and most copious antioxidants in the human diet. Diet may be considered as one of the essential factors in functionality, integrity, and composition of the gut microbiota as the gastrointestinal tract is the primary organ presented to parts of the eating regimen. A large number of polyphenols remains unabsorbed in the gastrointestinal tract and they may gather in large intestine, where most of them are widely metabolized by the intestinal microbiota. This gut health environment, while assuming basic functions for the support of the wellbeing of host, is presented to the effect of outer factors, including dietary patterns. To overcome the low bioavailability of dietary polyphenols, a few distinct methodologies have been developed to improve solvency and transport through gastrointestinal tract and convey it to targeted intestinal regions. Among the diverse dietary compounds, polyphenols establish a fascinating group as some of them have been found to present significant biological activities comprising antioxidant, anticarcinogenic or antimicrobial activities. Furthermore, it has effect on gut metabolism and immunity and apply anti-inflammatory properties. Formation of bioactive polyphenol-determined metabolites may likewise profit the wellbeing status of the subjects, although the mechanisms have not been defined. Notwithstanding, in spite of the fact that the incredible scope of health advancing activities of dietary polyphenols has been broadly explored, their impact on the adjustment of the gut biology and the two-way relationship between polyphenols and microbiota are still inadequately comprehended. In this review, we have focused on the impacts of polyphenols in a diet with biological activities, gut ecology and influence of their proportional connections in human wellbeing and disease.